Sarcoidosis and collagenous colitis - Important clinical association or coincidence? (Indian Journal of Case Reports, 2019)
We present a case of a 57-year-old woman with two rare concomitant diseases: Sarcoidosis and collagenous colitis. The patient was admitted to our hospital with the symptoms of watery diarrhea that intermittently lasted for years because of delayed diagnosis. Despite increasing awareness of microscopic colitis, the delayed diagnosis remains a major problem. The diagnosis was quickly confirmed with flexible proctosigmoidoscopy. Rectal biopsies were sufficient for the diagnosis. Symptoms improved by the 2nd day of the induction therapy with budesonide. The causal relationship between sarcoidosis and microscopic colitis is not yet confirmed, and to the best of our knowledge, this is the first such case report.